Pleistocene Archaeology - Migration, Technology, and Adaptation 2020
DOI: 10.5772/intechopen.93819
|View full text |Cite
|
Sign up to set email alerts
|

Island Migration, Resource Use, and Lithic Technology by Anatomically Modern Humans in Wallacea

Abstract: Island migration and adaptation including both marine and terrestrial resource use and technological development by anatomically modern humans (AMH) are among the most significant issues for Pleistocene archaeology in Southeast Asia and Oceania, and directly related to the behavioral and technological advancements by AMH. This paper discusses such cases in the Wallacean islands, located between the past Sundaland and the Sahul continent during the Pleistocene. The Pleistocene open sea gaps between the Wallacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Use-wear analysis conducted by the authors confirmed that the chert flakes associated with Anoa bone showed traces of impact on hard materials, most likely animal bones. The use-wear analysis also identified tools from the layers dated to around the end of the LGM displaying flat polishing and diagonal/ transversal striations and indicating prolonged contact with phytolith-rich plants through scraping [39,56].…”
Section: Goa Topogaro Complex In Sulawesi Islandmentioning
confidence: 96%
See 3 more Smart Citations
“…Use-wear analysis conducted by the authors confirmed that the chert flakes associated with Anoa bone showed traces of impact on hard materials, most likely animal bones. The use-wear analysis also identified tools from the layers dated to around the end of the LGM displaying flat polishing and diagonal/ transversal striations and indicating prolonged contact with phytolith-rich plants through scraping [39,56].…”
Section: Goa Topogaro Complex In Sulawesi Islandmentioning
confidence: 96%
“…Along these two routes, the oldest modern human traces were found in several cave sites in south Sulawesi in the form of rock paintings that were dated by U-series of speleothem covering the rock art to c. 43 ka [24,25], considerably earlier than the currently oldest C14 dates in south Sulawesi of up to 36 ka [26]. Other sites older than 30 ka in Wallacea along the northern routes are Golo Cave site in Gebe Island dated to c. 36 ka [27,28], Leang Sarru in Talaud Islands dated to 35 ka [29][30][31][32], Bubog I in Mindoro Island dated to >35 ka [33][34][35], and Goa Topogaro site in Central Sulawesi, which was previously dated to >30 ka [36][37][38][39]. All these sites produced no early modern human fossil remains.…”
Section: Two Possible Migration Routes By Modern Human In Wallaceamentioning
confidence: 99%
See 2 more Smart Citations
“…The second section "Pleistocene Human Migration and Adaptation in Southeast Asia" contains two papers on the prehistory of the Sunda shelf region and the Wallacean islands. Chapter 3 by Halmi Insani and Masanaru Takaki is entitled "Mainland versus Island Adaptation: Palaeobiogeography of Sunda Shelf Primates Revisited" and focuses on dispersal events and phylogeographic analysis of human and non-human primates in the Sunda shelf region and mainly the Malay Peninsula and the islands of Sumatra, Java, and Borneo [18]. Southeast Asian primates, including humans are one of the most successful mammals in responding to the dynamic palaeoclimatic changes since at least 1 mya, and human and non-human primates reflect the complex history of a wide range of ecological and geographic variation.…”
Section: Introduction Of the Chaptersmentioning
confidence: 99%